Mastering the market cycle : getting the odds on your side - Marks, Howard (Boston, Massachusetts : HarperCollins Publishers, 2018)
We all know markets rise and fall, but when should you pull out, and when should you stay in? The answer is never black and white, but is best reached through a keen understanding of the reasons behind the rhythm of cycles. Confidence about where we are in a cycle comes when you learn the patterns of ups and downs that influence not just economics, markets, and companies, but also human psychology and the investing behaviors that result.